Fatty Acid and Mineral Composition of Papua New Guinea Echinoderms - H., Maven; K., Sunder Rao; W., Benko; K., Alam; M.E., Huber; T., Rali; I., Burrows (Fishery Technology, 2025)
The fatty acid composition of three Holothuria spp. and one Bohadschia sp. were determined by gas liquid chromatography. Arachidonic acid (20:4n-5) was the predominant fatty acid (25.29-34.49%) in the three Holothuria spp. while eicosatrienoic (20:3n-6) was predominant in the Bohadschia sp. Docosahexaenoic acid (22:6n-3) and eicosapentaenoic acid (20:5n-3) concentrations were appreciable. The mineral (Na, K, Ca, Mg, Fe, Zn, Cu, Cd, Pb, Hg, As, Se) composition of the echinoderms were determined by Atomic Absorption Spectrophotometry. The alkali (Na and K) and alkaline (Ca andMg)metalswere abundant in the tissuewhile the heavymetals (Cu, Cd, Pb, Hg) and metalloids (As and Se)wereminor constituents.